Comparison of different designs of implant-retained overdentures and fixed full-arch implant-supported prosthesis on stress distribution in edentulous mandible - A computed tomography-based three-dimensional finite element analysis - Barão, V. A R [UNESP]; Delben, J. A. [UNESP]; Lima, J.; Cabral, T.; Assunção, Wirley Goncalves [UNESP] (Elsevier, 2013)
A finite element analysis was used to compare the effect of different designs of implant-retained overdentures and fixed full-arch implant-supported prosthesis on stress distribution in edentulous mandible. Four models of an human mandible were constructed. In the OR (O'ring) group, the mandible was restored with an overdenture retained by four unsplinted implants with O'ring attachment; in the BC (bar-clip) -C and BC groups, the mandibles were restored with overdentures retained by four splinted implants with bar-clip anchor associated or not with two distally placed cantilevers, respectively; in the FD (fixed denture) group, the mandible was restored with a fixed full-arch four-implant-supported prosthesis. Models were supported by the masticatory muscles and temporomandibular joints. A 100-N oblique load was applied on the left first molar. Von Mises (σvM), maximum (σmax) and minimum (σmin) principal stresses (in MPa) analyses were obtained. BC-C group exhibited the highest stress values (σvM=398.8, σmax=580.5 and σmin=-455.2) while FD group showed the lowest one (σvM=128.9, σmax=185.9 and σmin=-172.1). Within overdenture groups, the use of unsplinted implants reduced the stress level in the implant/prosthetic components (59.4% for σvM, 66.2% for σmax and 57.7% for σmin versus BC-C group) and supporting tissues (maximum stress reduction of 72% and 79.5% for σmax, and 15.7% and 85.7% for σmin on the cortical and trabecular bones, respectively). Cortical bone exhibited greater stress concentration than the trabecular bone for all groups. The use of fixed implant dentures and removable dentures retained by unsplinted implants to rehabilitate edentulous mandible reduced the stresses in the periimplant bone tissue, mucosa and implant/prosthetic components. © 2013 Elsevier Ltd.
Keywords: Biomechanics; Dental Implants; Finite element analysis; Fixed full-arch prosthesis; Overdenture; Implant-supported prosthesis; Masticatory muscles; Peri-implant bones; Principal stress; Temporomandibular joint; Three dimensional finite element analysis; Trabecular bones; Arches; Bone; Computerized tomography; Dental prostheses; Finite difference method; Finite element method; Restoration; Stress concentration; Tissue; Prosthetics; bone stress; compressive stress; computer assisted tomography; controlled study; cortical bone; dental abutment; dental retainer; edentulousness; equipment design; finite element analysis; human; mandible prosthesis; mandible reconstruction; mechanical stress; overlay denture; priority journal; process design; removable partial denture; stress distibution; three dimensional imaging; trabecular bone